2016
DOI: 10.1161/jaha.116.004017
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Silencing Blunts the Slow Force Response to Myocardial Stretch

Abstract: BackgroundMyocardial stretch increases force biphasically: the Frank‐Starling mechanism followed by the slow force response (SFR). Based on pharmacological strategies, we proposed that epidermal growth factor (EGF) receptor (EGFR or ErbB1) activation is crucial for SFR development. Pharmacological inhibitors could block ErbB4, a member of the ErbB family present in the adult heart. We aimed to specifically test the role of EGFR activation after stretch, with an interference RNA incorporated into a lentiviral v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
9
0
2
Order By: Relevance
“…The ErbB receptor tyrosine kinase family consists of four members, ErbB1 (epidermal growth factor receptor, EGFR), ErbB2, ErbB3, and ErbB4, which are expressed on a plethora of cell types, including epithelial [1], endothelial [2], neuronal and glial [3], bone [4], adipose [5], liver [6], and cardiovascular cells [7]. Following ligand binding and activation, oligomerisation of ErbB family members occurs [8].…”
Section: Erbb Receptors a Gatekeeper Of Infectious Diseasementioning
confidence: 99%
“…The ErbB receptor tyrosine kinase family consists of four members, ErbB1 (epidermal growth factor receptor, EGFR), ErbB2, ErbB3, and ErbB4, which are expressed on a plethora of cell types, including epithelial [1], endothelial [2], neuronal and glial [3], bone [4], adipose [5], liver [6], and cardiovascular cells [7]. Following ligand binding and activation, oligomerisation of ErbB family members occurs [8].…”
Section: Erbb Receptors a Gatekeeper Of Infectious Diseasementioning
confidence: 99%
“…105 Thus, investigations have examined the role that EGFR transactivation plays in the SFR. EGFR phosphorylation measurably increases in response to stretch 86 and, in those cases where EGFR or the signalling pathway components immediately upstream or downstream are inhibited, 91,103,106 the SFR is blunted. The SFR 91 and increased EGFR phosphorylation 107 are prevented when the Src tyrosine kinase is blocked.…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%
“…oxygen species EGFR 91,108 and GPCR 93,109-111 agonists increase nicotinamide adenine dinucleotide phosphate (NADPH) oxidase-dependent reactive oxygen species (ROS) production. 103,112,113 Compromising EGFR or its mediators suppresses Ang II/ET-1-induced ROS formation 91,106 and, more relevantly, ROS production increases in response to stretch. 22,24,116 Prosser et al 24 demonstrated that this stretch-induced upregulation of NADPH oxidase activity was likely due, at least in part, to mechanical transduction of stretch via microtubules as well as the aforementioned GPCR pathway.…”
Section: Nadph Oxidase-derived Reactivementioning
confidence: 99%
“…3.13 donde se observa la producción de ROS tanto en cardiomiocitos aislados como en tejido ventricular. El factor de crecimiento epidérmico (EGF) fue considerado activador de la NOX en tejido cardíaco (Nolly, Caldiz et al 2014, Brea, Diaz et al 2016. En nuestro trabajo el inhibidor del EGFR, AG1478 impide la producción de ROS a partir de NADPH oxidasa, indicando que el EGFR se encontraría corriente arriba de la misma en esta vía.…”
Section: -Discusiónunclassified